Beneficiary satisfaction with mobile medical units in the state of Andhra Pradesh - Nair, Amrutha; Raikwar, Aakash A.; Wassey, M. Abdul; Dogra, Vishal (International Journal Of Community Medicine And Public Health, 2020)
Background: Mobile health services in India have gained significant attention recently. However, there is little information regarding the beneficiary satisfaction of such services. Beneficiaries’ satisfaction and perception plays significant role in utilization of services. We assess the program beneficiaries’ satisfaction of using mobile health services in rural Andhra Pradesh. Methods: We used a cross-sectional study design to survey the mobile health services program beneficiaries in rural Andhra Pradesh (October 2016 to October 2018). Beneficiaries availing the mobile health services from 277 mobile medical vans across 13523 villages were selected using multistage sampling. Exit interviews (using Likert-scale questions) were used to reveal the ease of access in utilising mobile health services and satisfaction among the program beneficiaries. Results: A total, 1080 exit interviews were conducted. Above ninety percent of beneficiaries completed the exit interviews (response rate: 95%). More than two-thirds (72%) of the respondents were females and aged >45 years (71%). Of all respondents, the majority were Hindu (89%), belonging to socially disadvantaged groups (80%), and illiterate (56%). Nearly all (95%) program beneficiaries found mobile health services easily accessible and building their knowledge and awareness (94%) on key health issues. Ninety-five percent of the program beneficiaries strongly favoured recommending the use of mobile health services to others. The overall satisfaction rate was 95% (Cronbach alpha 0.925). Conclusions: Mobile health services in rural areas are effective in meeting the beneficiaries’ expectations. High beneficiary satisfaction and trust in mobile health services strongly favours such services in other rural geographies.